A multidimensional analysis of spatial order in public spaces: a case study of the town Morąg, Poland - Szczepańska, Agnieszka; Pietrzyk, Katarzyna (Bulletin of Geography. Socio-economic Series, 2019)
Centrally located public spaces, such as old towns, are an important feature of historic towns. They are often the most characteristic and representative element of a town that brings together members of the local community, plays various sociological and social roles and promotes direct interactions between the users of space. Only high-quality public spaces can effectively fulfil their role. The aim of this study was to analyse spatial order in public spaces on the example of the Old Town district of Morąg in North-Eastern Poland. The quality of public spaces was analysed with the use of a self-designed method, a field inventory and a questionnaire survey involving 100 members of the local community who were asked to evaluate the quality of public spaces in the town. The results of the comparison were used to identify public spaces that require revitalisation. The study demonstrates that spatial order directly influences the quality of public spaces. Our findings indicate that multidimensional analyses of spatial order and opinion surveys provide valuable inputs and should be included in studies evaluating the quality of public spaces.